Analysis on Scopus Articles Padang State University Based on SINTA Website - Kerin Hagia Aidillah; Dodi Vionanda; Dony Permana (Departemen Statistika Universitas Negeri Padang, 2025)
Universities have the responsibility to carry out education, research, and community service as mandated by Law Number 20 of 2003 on the National Education System in Article 20. The flagship research theme set by Universitas Negeri Padang (UNP) for the period 2020-2024 is